Mammoth Fauna Remains From Late Pleistocene Deposits of the Dmitry Laptev Strait South Coast (Northern Yakutia, Russia) - Kuznetsova, Tatiana V.; Wetterich, Sebastian; Matthes, Heidrun; Tumskoy, Vladimir E.; Schirrmeister, Lutz (Frontiers in Earth Science, 2022)
The Yedoma Ice Complex in northern Yakutia provides perfect preservation conditions for frozen remains of vertebrate animals. Even complete mummified specimens of the late Pleistocene Beringian Mammoth fauna such as woolly mammoth, woolly rhinoceros, horse, and bison are occasionally found in permafrost deposits across eastern Siberia, i.e. in West Beringia, although bone findings are much more common. The present study characterizes mammal bone findings from late Pleistocene and Holocene permafrost deposits exposed at the Oyogos Yar coast at the southern shore of the Dmitry Laptev Strait that connects the Laptev and East Siberian seas. The study applies a method to differentiate fossil bone samples by the location of their finding and by the accuracy of their relation to a depositional horizon. We analyzed a total of 38 finite radiocarbon ages of bone material from mammoth, horse, and muskox spanning from about 48.8 to 4.5 ka BP, including both our own data and literature data in addition to previous publications that report numerous bones with infinite ages from the Oyogos Yar coast. The distribution of bone material along the coastal permafrost exposure is not uniform; it depends upon whether the material was found in situ, on thermo-terraces, or on the shore. The overall bone collection consists of 13 species of which Mammuthus primigenius (woolly mammoth, 41%), Bison priscus (bison, 19%), Equus ex eg. caballus (horse, 19%), and Rangifer tarandus (reindeer, 16%) predominate. The fossil bone species distribution is similar to those of other prominent Yedoma outcrops in the region, i.e. on Bykovsky Peninsula and on Bol’shoy Lyakhovsky Island. Correlation analysis shows that the Oyogos Yar bone sampling sites of different geomorphological settings are similar to each other but not to all sample sites within the other two locations on Bykovsky Peninsula and on Bol’shoy Lykahovsky Island. High similarities in terms of correlation coefficients between specific sample sites are often not represented in the cluster analysis.